Deep support vector machine for hyperspectral image classification. (July 2020) - Okwuashi, Onuwa; Ndehedehe, Christopher E.
Highlights: Deep Support Vector Machine (DSVM) introduced in hyperspectral image classification. DSVM outperformed five other classification algorithms, including Deep Neural Network. DSVM is a state-of-the-art algorithm to improve hyperspectral image classification. Abstract: To improve on the robustness of traditional machine learning approaches, emphasis has recently shifted to the integration of such methods with Deep Learning techniques. However, the classification problems, complexity and inconsistency in several spectral classifiers developed for hyperspectral images are some reasons warranting further research. This study investigates the application of Deep Support Vector Machine (DSVM) for hyperspectral image classification. Two hyperspectral images, Indian Pines and University of Pavia are used as tentative test beds for the experiment. The DSVM is implemented with four kernel functions: Exponential Radial Basis Function (ERBF), Gaussian Radial Basis Function (GRBF), neural and polynomial. Stand-alone Support Vector Machines form the interconnecting weights of the entire network. The network is trained with one hundred input datasets, and the interconnecting weights of the network are initialised using the regularisation parameter of the model. Numerical results show that the classification accuracies of the DSVM for Indian Pines and University of Pavia based on each DSVM kernel functions are: ERBF (98.87%, 98.16%), GRBF (98.90%, 98.47%), neural (98.41%, 97.27%), and polynomial (99.24%, 98.79%). By comparing the DSVM algorithm against well-known classifiers, Support Vector Machine (SVM), Deep Neural Network (DNN), Gaussian Mixture Model (GMM), K Nearest Neighbour (KNN), and K Means (KM) classifiers, the mean classification accuracies for Indian Pines and University of Pavia are: DSVM (98.86%, 98.17%), SVM (76.03%, 73.52%), DNN (94.45%, 93.79%), GMM (76.82%, 78.35%), KNN (76.87%, 78.80%), and KM (21.65%, 18.18%). These results indicate that the DSVM outperformed the other classification algorithms. The high accuracy obtained with the DSVM validates its efficacy as state-of-the-art algorithm for hyperspectral image classification.